Celebrity Endorsement on Purchasing Decisions with Brand Trust as a Mediator - Nandini, Nur Intan Mutiara; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This study aims to determine how much influence Celebrity Endorsement has on Purchasing Decisions with Brand Trust as a Mediator for X Skincare Product Users in Semarang City. This study uses a quantitative approach using primary data obtained from distributing written instruments or questionnaires and getting responses from respondents as many as 100 samples using the survey method. In this study, to evaluate the hypothesis using SmartPLS (Partial Least Square) V4.1 Analysis. Based on the results of the SmartPLS analysis test that has been carried out, the results show that Celebrity Endorsement (X) has a positive and significant effect on Purchasing Decisions (Y), Celebrity Endorsement (X) has a positive and significant effect on Brand Trust (Z), Brand Trust (Z) has a positive and significant effect on Purchasing Decisions (Y), Brand Trust (Z) has a positive and significant effect on mediating between Celebrity Endorsement (X) on Purchasing Decisions (Y).